PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP KOMPETENSI PEGAWAI DINAS PERHUBUNGAN KABUPATEN KUTAI KARTANEGARA - muhammad Subandi (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2016)
To support the development of Kutai regency in the field of transportation required the competent staff of Department of Transportation. To realize Employees are competent, one of them through education and training. Training activities is the process of improving employee competencies through the transfer of knowledge, attitudes and skills to be capable to do the job. This study aims to determine the influence of Education and Training of Employee Competency. The research method using associative method with quantitative approach, the analysis of research data using simple regression formula, and hypothesis testing formula product moment correlation and t test. The sample in this study was 60 Employees. From the analysis of correlation Product Moment correlation is 0,556 (medium category). Because the count r price (0,556)> r table (0254), it was concluded that there is a positive and significant influence amounted to 0,556 between Competence Education and Training of Employees. Then the coefficient of determination (Rsquare) = 0.5562 = 0,309x100 = 30.87%, so the contribution of education and training of the Employee Competence amounted to 30.87%, while 69.13% Employee Competency explained by other variables. Furthermore, the results of calculations performed by t test obtained t arithmetic (4.398)> t table (1.671). Thus the hypothesis is accepted because it has been proven true, that t is greater than t table.Keywords: Education and Training, Competence